Sistem Penyimpanan Arsip Dinamis Inaktif pada Bagian Hukum di Pengadilan Tinggi Padang - Silfiyanti Silfiyanti; Marlini Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This article aims to describe: (1) what is the state of inactive records storage systems at Padang high court of law will be undertaken by archivists; (2) what is the process of inactive records storage systems at Padang high court of law will be undertaken by archivists; and (3) what are the problem and efforts in a process of inactive records storage system at padang high courth of law will be undertaken by archivists. Data were collected through direct observation and interviews with archivists and employees that exist at the Legal Division High Court Padang. Analyzing data descriptively. Based on the results of the research, concluded the following. The first is archival storage system on the Law of using three systems, namely the number system, subject system and chronological system. The second is archival storage procedures on the Law of the High Court of Padang which receives the case file to be saved from the clerk, upon receipt of the file examined the completeness of its contents, if it has been completed then recorded in the register parent book, the last step is inserting into the archives box and store it in shelf archive. The third is the constraint in archival storage section Padang High Court Law that the room is too small, lack the archival storage box, lack of air conditioners like air-conditioning and Fan, and the lack of filing cabinets or shelves. Keywords: systems, storage, archives, dynamic, inactive